Avaliação dos efeitos do exercício de força agudo e crônico sobre a reatividade uterina de ratas Wistar e efeito preventivo da Spirulina platensis - Ferreira, Paula Benvindo (2019)
The benefits of exercise in physical and mental health are well established as an alternative to maintaining well-being and as a means to reduce the risk of various chronic diseases. However, when it is not prescribed correctly, it is associated with oxidative stress, involved in the pathophysiology of disorders in the female reproductive system. In this context, Spirulina platensis, an algae with antioxidant potential, promoted beneficial effects in smooth muscle models. Thus, aiming at the search for new therapeutic alternatives, we evaluated the effects of acute and chronic strength exercise and a possible preventive effect of S. platensis on the rat uterus. The experimental procedures were approved by CEUA/UFPB (certificate 0211/14). The animals were divided into saline (GS) and supplemented with S. platensis at doses of 50 (GSP50) and 100 mg / kg (GSP100), only adapted group (CG, control), exercised groups and euthanized immediately (GO), 12 hours (G12) and 24 hours after exercise (G24), group trained for 8 weeks (GT) and supplemented with algae at the dose of 50 (GT50) and 100 mg / kg (GT100). The contractile and relaxing reactivity of the uterus, the oxidative stress balance / systemic and tissue antioxidant defenses, the pathway modulation of the mitogen activated proteins kinases (MAPK) and the histomorphometric parameters of the uterus and adrenal gland were evaluated. It was observed that a single strength exercise session increased contractile reactivity, decreased uterine relaxant reactivity, without altering tissue oxidative stress or MAPK pathway, decreased eosinophil number, increased vascularity and area of the uterine muscular layer, contributing to the increase of the contractile reactivity, besides an increase of the cortical area of the adrenal, suggestive of increased production of catabolic hormones, such as cortisol. Considering the differences between the acute and chronic physiological responses of exercise and that strength training induces an increase in oxidative stress, in recent years the consumption of antioxidant supplements has been shown to be a useful non-invasive tool to decrease the muscle damage, improve exercise performance, prevent or reduce oxidative stress. Thus, we hypothesized that strength training would induce changes in uterine reactivity through increased oxidative stress and that algae supplementation would prevent such effects. It has been observed that strength training increases the contractile efficacy, decreases the relaxing potency and that these effects are prevented by dietary supplementation with S. platensis, by inhibition of cyclooxygenase pathway, increase in NO bioavailability and reactive oxygen species ; In addition, it prevents the decrease of JNK expression, suggesting an anti-inflammatory role of both exercise and supplementation with S.platensis and increases vascularization and vascular area and prevents the reduction of myometrial thickness, besides partially preventing the increase of fasciculated area and lipid degeneration, demonstrating a protective role against the release of catabolic hormones such as cortisol. Therefore, the uterus is highlighted as a target organ for the exercise, as well as showing that the exercise of acute and chronic strength alter uterine reactivity and food supplementation with algae prevents the damages associated with strength training revealing the potential promising dietary supplementation with S. platensis in pathophysiological processes that involve deregulation in contractile uterine homeostasis and as a preventive for women who practice intense physical activity.